Severe acute respiratory syndrome coronavirus 2 as a potential cause of type 1 diabetes facilitated by spike protein receptor binding domain attachment to human islet cells: An illustrative case study and experimental data. Issue 11 (10th June 2021) - Venkatesh, Nisha; Astbury, Natalie; Thomas, Merlin C.; Rosado, Carlos J.; Pappas, Evan; Krishnamurthy, Balasubramanian; MacIsaac, Richard J.; Kay, Thomas W. H.; Thomas, Helen E.; O'Neal, David N.
Abstract: Aims: Aim of this study is to report severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, responsible for coronavirus disease 2019 (COVID‐19), as a possible cause for type 1 diabetes by providing an illustrative clinical case of a man aged 45 years presenting with antibody‐negative diabetic ketoacidosis post‐recovery from COVID‐19 pneumonia and to explore the potential for SARS‐CoV‐2 to adhere to human islet cells. Methods: Explanted human islet cells from three independent solid organ donors were incubated with the SARS‐CoV‐2 spike protein receptor biding domain (RBD) fused to a green fluorescent protein (GFP) or a control‐GFP, with differential adherence established by flow cytometry. Results: Flow cytometry revealed dose‐dependent specific binding of RBD‐GFP to islet cells when compared to control‐GFP. Conclusions: Although a causal basis remains to be established, our case and in vitro data highlight a potential mechanism by which SARS‐CoV‐2 infection may result in antibody‐negative type 1 diabetes.